Daijin’s Moral Responsibility in Suzume no Tojimari (2022) - Alvina Salshabilla Linjani Putri; Muhammad Ilham Rahmansyah; Dian Oktavia; Happy Julia Rahmadianti; Rommel Utungga Pasopati; Anicleta Yuliastuti (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2026)
This study explores the concept of moral responsibility through the character of Daijin in the animated film Suzume no Tojimari. This study was conducted because there are still few studies that highlight how animated films depict moral responsibility, especially through non-human characters. By analyzing Daijin’s actions, decisions, and their consequences, the research examines how moral agency is portrayed in a fantastical setting. Using textual analysis through qualitative method, the study identifies key themes such as duty, sacrifice, and the conflict between personal desires and collective well-being. The findings reveal that Daijin’s transformation from a reluctant guardian to a figure of responsibility that does personal sacrifice reflects moral responsibility, including reasons-responsiveness, forward-looking responsibility, and reactive attitudes. This study is expected to contribute to moral and film studies by showing that animated films can also be a means of learning ethical values. In conclusion, Suzume no Tojimari offers a thought-provoking exploration of moral responsibility. Daijin's storyline serves as a powerful reminder of the complexities inherent in navigating ethical dilemmas, especially when faced with choices that impact both personal and collective fates.